HUBUNGAN RIWAYAT PEMBERIAN ASI EKSLUSIF DAN KETEPATAN PEMBERIAN MAKANAN PENDAMPING ASI (MPASI) DENGAN KEJADIAN STUNTING - ravi masitah (IKesT Muhammadiyah Palembang, 2023)
Introduction : Stunting is a kind of malnutrition caused by chronic nutritional deficiencies that start before pregnancy, during pregnancy and after childbirth. Stunting causes inhibition of children's growth and unproductive in adulthood. Exclusive breastfeeding for babies can prevent infection and fulfill nutritional needs based on their age. Complementary feeding is given after the baby is 6 months old because breast milk cannot fulfill the nutritional needs of the child. Children who are given complementary feeding early can cause a high incidence of infections such as diarrhea, respiratory infections, allergies and growth disorders because the digestive system is not functioning properly. Objective : The purpose of the research was a correlation of exclusive breastfeeding history and the accuracy of complementary feeding with the incidence of stunting. Methods : The study was conducted in Kuto Batu village in March-June 2022. The research subjects were 10 mothers who had stunted toddlers as a case group and 10 mothers who had normal nutritional status toddlers as a control group who fulfill the inclusion and exclusion criteria. The data was analyzed using the chi square test. Conclusion : The results showed that there was a correlation of exclusive breastfeeding history and the accuracy of complementary feeding with the incidence of stunting p-value <0.05. Mothers who provide exclusive breastfeeding and appropriately provide complementary feeding to children on the age of 6 months, can prevent children from various nutritional problems especially stunting.